Overview Of Pregnant Women's Knowledge About Fe Tablets In The Working Area Of Mpunda Health Center, Bima City, 2023 - Yati Purnama; Eti Noviatul Hikmah (Sean Institute, 2023)
At the Mpunda Community Health Center, Bima City, data shows that anemia in pregnant women in 2019 was 122 cases, then increased in 2020 to 156 cases and decreased again in 2021 to 100 cases. In 2022, data was obtained on 76 cases of pregnant women with anemia, then in 2023, for the period January to June, data was obtained on 36 cases of pregnant women with anemia (Mpunda Community Health Center, Bima City, 2023). RESEARCH OBJECTIVE: To analyze the description of knowledge of pregnant women about Fe tablets in the Mpunda Community Health Center working area, Bima City in 2023. RESEARCH METHOD: This type of research is quantitative research, descriptive correlational research design with a cross sectional approach. The population in this study was 392 pregnant women in the Mpunda Health Center working area in Bima City in 2023. Samples were taken from 80 pregnant women using purposive sampling technique. RESEARCH RESULTS: The research results included pregnant women in the high risk age category (<20 years or >35 years), namely 25 people (31.2%) and the age category that was not at risk, namely 55 people (68.8%). Based on basic education level, there are 20 people (25%), and those with higher education are 60 people (75%). Based on the occupational group, those who are not working (IRT) are 75 people (93.8%), and those who are not working are 5 people (6.2%). Based on the knowledge of pregnant women, those with good knowledge were 41 people (51.2%), those with sufficient knowledge were 31 people (38.8%), and those with poor knowledge were 8 people (10%).